SMARTPAI-Based TPACK Optimization for PAI Teachers in Implementing a Love-Based Curriculum - Siti Khoiriyah; Saeful Anwar; Usman Ro'in (Universitas Nurul Jadid, 2026)
The digital transformation of education demands that Islamic Religious Education (PAI) teachers holistically integrate technology, pedagogy, and subject content. Field observations at MTs Islamiyah Balen, Bojonegoro, revealed that PAI teachers still rely predominantly on conventional lecture methods, have limited confidence in classroom technology use, and lack structured frameworks for designing value-based learning. This condition creates a gap between the humanistic demands of the Love-Based Curriculum and actual instructional practice. The community service program was implemented through a Participatory Action Research (PAR) approach comprising four stages: needs analysis, TPCK integration training, SMARTPAI application mentoring, and collaborative monitoring and evaluation. Partner teachers participated actively as co-collaborators at every stage. The results demonstrate measurable improvements: at least 75% of PAI teachers adopted SMARTPAI for material delivery and digital assessment; interactive media use increased to 2-4 sessions per thematic unit; each teacher developed a minimum of three digital content items; 85% of TPCK-based teaching modules were developed and 70% were implemented with a differentiated approach; and professional collaboration meetings were held monthly. These achievements indicate a significant shift from teacher-centered toward learner-centered instruction, fostering more dialogical, contextual, and character-oriented learning. Ongoing mentoring remains necessary to sustain consistency and deepen value internalization.